Broken piece of a hero stone - Temples of India Project Team (Jio Institute, 2024)
Seen here is a broken piece of a hero stone, once part of the temple’s architectural structure. Despite its fragmented state, it is now worshipped among the veeron ke pathar (stones of the heroic people). In its current aniconic form, this fragment receives the same reverence and rituals as the other fragments kept alongside.